Ultra Massive Passive Galaxies at z 1.7. Issue Volume 11:Issue S319(2015) (17th August 2016) - Arcila-Osejo, Liz; Sawicki, Marcin; Golob, Anneya; Arnouts, Stephane; Moutard, Thibaud
Abstract: At redshift z 1.7 the Universe was at the peak of its star-formation activity. It is thus a puzzle why some galaxies, many of them very massive (M* ⩾ 10 11 M⊙), had already chosen to stop forming stars. These ultra-massive galaxies, guaranteed to be the central galaxies of their host dark matter halos, must have attained very high rates of star formation to assemble their stellar masses in such a short amount of time. Using the largest (to date) K-selected gzK s survey of passive galaxies (in an effective area of 27.5 deg 2 ) we study the demographics of these dead monsters, hoping to help understand the quenching mechanism that shut them down.